Konstruksi Perempuan Dan Relasi Kekuasaan Dalam Sastra Indonesia: Perspektif Kritik Feminisme - Bima Sastra (CV. SINAR HOWUHOWU, 2026)
This study aims to examine the construction of women and power relations in Indonesian literature using a feminist criticism perspective. Literature is viewed as a medium of social representation that both reflects and shapes societal perceptions of women. This research employs a qualitative approach with textual analysis of Indonesian literary works that position female characters as central elements of the narrative. The research data consist of narrative excerpts, dialogues, and character descriptions analyzed to reveal forms of female representation, mechanisms of patriarchal domination, and strategies of resistance presented in the texts. The findings indicate that women are still frequently constructed in subordinate positions through gender stereotypes and unequal power relations. However, there is a growing tendency for the emergence of female characters who demonstrate critical awareness and agency in confronting patriarchal structures. This study affirms that feminist criticism is a relevant approach for uncovering power relations in literature and for providing a more equitable understanding of women’s representation in the context of Indonesian literature.